Model Pengembangan Produk Jasa Baru pada Perusahaan Jasa Logistik - Sudrajat, Darjat (Binus Business Review, 2013)
The process of developing new product/service is a very important activity in every company, not only in manufacturing but also in corporate services company. Every successful company in new product development activities usually does in gradual and continuous process and supported by effective development organization in managing new products. Experiences and learning assist each company in the process of new product development in sustainable manner. Extensive studies on customers and potential customers as well as the competition are vital in managing the development of new product/service effective. Logistics Service Provider in Indonesia would also require the development of new product/service in order to survive, and even thrive in the midst of constantly increasing competition from local and multinational companies. To be able to process them effectively and efficiently, it needs a model that fits the characteristics of business and industry. Due to existing concepts in the development of new product/service is different, problems arise in accordance to concept of the industry. Thus, the purpose of this study is to obtain a model of the development of new product/service appropriate to apply in the logistic service industries. The study was conducted by in-depth interview to some logistic service providers and then relate it to the existing concepts. Then, it is obtained a model of the development of new product/service appropriate to relevant industries. Logistic product/service varies widely, depending on the needs or requirements of the consumers. Based on the results of the research of some logistic service providers and the study on the Â existing conceptual models, process models of new product development services on logistic service companies include identifying customer needs, requirement analysis, service design, service selection, service implementation, market launch, dan performance evaluation stages.